Outcome of hospitalization for COVID-19 in patients with interstitial lung disease: an international multicenter study - Drake, Thomas M.; Docherty, Annemarie B.; Harrison, Ewen M.; Quint, Jennifer K.; Adamali, Huzaifa; Agnew, Sarah; Babu, Suresh; Barber, Christopher M.; Barratt, Shaney; Bendstrup, Elisabeth; Bianchi, Stephen; Villegas, Diego Castillo; et al. (American journal of respiratory and critical care medicine, 2020)
Rationale: The impact of coronavirus disease (COVID-19) on patients with interstitial lung disease (ILD) has not been established. - - Objectives: To assess outcomes in patients with ILD hospitalized for COVID-19 versus those without ILD in a contemporaneous age-, sex-, and comorbidity-matched population. - - Methods: An international multicenter audit of patients with a prior diagnosis of ILD admitted to the hospital with COVID-19 between March 1 and May 1, 2020, was undertaken and compared with patients without ILD, obtained from the ISARIC4C (International Severe Acute Respiratory and Emerging Infection Consortium Coronavirus Clinical Characterisation Consortium) cohort, admitted with COVID-19 over the same period. The primary outcome was survival. Secondary analysis distinguished idiopathic pulmonary fibrosis from non-idiopathic pulmonary fibrosis ILD and used lung function to determine the greatest risks of death. - - Measurements and Main Results: Data from 349 patients with ILD across Europe were included, of whom 161 were admitted to the hospital with laboratory or clinical evidence of COVID-19 and eligible for propensity score matching. Overall mortality was 49% (79/161) in patients with ILD with COVID-19. After matching, patients with ILD with COVID-19 had significantly poorer survival (hazard ratio [HR], 1.60; confidence interval, 1.17-2.18; P = 0.003) than age-, sex-, and comorbidity-matched controls without ILD. Patients with an FVC of <80% had an increased risk of death versus patients with FVC ≥80% (HR, 1.72; 1.05-2.83). Furthermore, obese patients with ILD had an elevated risk of death (HR, 2.27; 1.39−3.71). - - Conclusions: Patients with ILD are at increased risk of death from COVID-19, particularly those with poor lung function and obesity. Stringent precautions should be taken to avoid COVID-19 in patients with ILD.
Gesehen am 02.02.2022
Frontdoor nennt 401 Autoren, pdf 70